Microwave Synthesize Karaya Gum-Cu, Ni Nanoparticles Based Bionanocomposite as an Adsorbent for Malachite Green Dye: Kinetics and Thermodynamics - Saruchi,; Kumar, Vaneet; Ghfar, Ayman A.; Pandey, Sadanand (Frontiers in Materials, 2022)
A novel approach was used to synthesize karaya gum-Cu, Ni nanoparticles based bionanocomposite by microwave irradiation method. Synthesized bionanocomposite was characterized by different techniques like Fourier transform infrared spectroscopy (FTIR), Field Emission scanning electron microscopy (FESEM), X-ray diffraction (XRD), High Resolution Transmission Electron Microscopy (HR-TEM), and Energy Dispersive X-Ray Analysis (EDX). The optimized condition for Karaya Gum-Cu-Ni–Bionanocomposite synthesis was the amount of solvent 4 ml, pH 10, time 20 s, power 100 W, monomer, and cross-linker concentration 14.11 mol L-1 and 0.1135 mol L-1, respectively. The maximum % swelling was found to be 1,176%. Different reaction parameters were optimized to get the maximum adsorption of malachite green dye. The maximum dye adsorption was found to be 94.1%. Different models for kinetics and isotherms were applied to analyze the adsorption data. Malachite green sorption onto bionanocomposite is best defined by pseudo second order kinetics, signifying that the dye uptake by the nanocomposite was organized by chemisorption method involving sharing of electrons in-between the cationic part of the dye as well as the anionic part of the bionanocomposite. Correlation coefficient (R2) was close to unity (0.99569). The R2 values of nanocomposite best fit in the Freundlich adsorption isotherm. The study confirmed the synthesized bionanocomposite was an efficient adsorbent for the adsorption of the harmful malachite green dye.